2020
DOI: 10.33096/whj.v1i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Atopik

Abstract: Dermatitis atopik (DA) atau atopik eczema adalah peradangan kulit berupa dermatitis yang kronis residif, disertai rasa gatal, dan mengenai bagian tubuh tertentu terutama di wajah pada bayi (fase infantil) dan bagian fleksural ekstremitas (pada fase anak). Dermatitis atopik kerap terjadi pada bayi dan anak, sekitar 50% menghilang pada saat remaja, kadang dapat menetap, atau bahkan baru mulai muncul saat dewasa. Peningkatan insidensi DA kemungkinan disebabkan oleh beberapa faktor misalnya urbanisasi, polusi, dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
2
1
1
Order By: Relevance
“…12 This research is also in line with the opinion (Susanto, 2013: Djuanda, 2010: Abdi, 2020: Judarwanto, 2000) which says that atopic dermatitis is an allergic disease that is believed to be genetic or hereditary that often occurs in families whose family members who have a history of atopian in the family such as allergic rhinitis and or bronchial asthma. 12,13,14 According to Susanto, (2013) atopic dermatitis is a disease that is often believed to be genetic/hereditary and often occurs in families whose family members also have asthma disorders, itching rashes are mainly seen on the scalp, neck, elbows, back of the knees, buttocks and other studies that conclude that the decline in atopic dermatitis is maternal. 24 It is well known the link between atopic dermatitis, bronchial asthma, and allergic rhinitis due to atopic dermatitis, bronchial asthma, and allergic rhinitis also referred to as Triassic Atopic.…”
Section: Characteristics Of Respondentssupporting
confidence: 82%
See 4 more Smart Citations
“…12 This research is also in line with the opinion (Susanto, 2013: Djuanda, 2010: Abdi, 2020: Judarwanto, 2000) which says that atopic dermatitis is an allergic disease that is believed to be genetic or hereditary that often occurs in families whose family members who have a history of atopian in the family such as allergic rhinitis and or bronchial asthma. 12,13,14 According to Susanto, (2013) atopic dermatitis is a disease that is often believed to be genetic/hereditary and often occurs in families whose family members also have asthma disorders, itching rashes are mainly seen on the scalp, neck, elbows, back of the knees, buttocks and other studies that conclude that the decline in atopic dermatitis is maternal. 24 It is well known the link between atopic dermatitis, bronchial asthma, and allergic rhinitis due to atopic dermatitis, bronchial asthma, and allergic rhinitis also referred to as Triassic Atopic.…”
Section: Characteristics Of Respondentssupporting
confidence: 82%
“…18 Data from one study showed the order of allergens that are often found and skin tests react positively to atopic dermatitis are eggs (69%), cow's milk (52%), peanuts (42%), soy (34%), and wheat 33%, and others against fish (seafood), chicken, snacks/snacks containing (monosodium glutamate) and the prevalence of food allergies are found in 40% of cases of atopic dermatitis. 12,19 It was also found in this study from 156 (75.0%) respondents who did not have food allergy factors there were 52 (25.0%) respondents with atopic dermatitis. Because food allergies are not always the cause of atopic dermatitis, it can be caused by other factors, in this study other factors that can cause atopic dermatitis are genetic factors recorded by as many as 34 respondents and environmental factors by as many as 18 respondents.…”
Section: Characteristics Of Respondentssupporting
confidence: 71%
See 3 more Smart Citations